An increase in nitric oxide produced by rat peritoneal neutrophils is not involved in cell apoptosis. Issue 3 (1995) - Fierro Fierro, I. M. I. M.; Barja-Fidalgo Barja-Fidalgo, C. C.; Canedo Canedo, R. M. R. M.; Cunha Cunha, F. Q. F. Q.; Ferreira Ferreira, S. H. S. H.
Abstract : Polymorphonuclear neutrophils (PMN) obtained from carrageenin-stimulated peritoneal cavities of rats, but not blood PMN, spontaneously produced nitric oxide (NO) when incubated in vitro . Incubation of the cells with the NO synthase inhibitors, L-imino-ethyl-L-ornithine (L-NIO) or N G -monomethyl-L-arginine (L-NMMA), inhibited NO production. This inhibition could be reversed by L-arginine. Incubation of PMN with lipopolysaccharide (LPS) failed to enhance NO production. Pretreatment of the rats with dexamethasone (DEXA) prior to carrageenin injection or incubation of PMN with the glucocorticoid in vitro partially inhibited the spontaneous release of NO. On the other hand, when PMN obtained from DEXA pretreated rats were incubated in vitro with DEXA, NO synthase activity and hence NO generation were almost abolished. A similar inhibition was also observed following the addition of L-NIO or cycloheximide to cultures of carrageenin-elicited PMN. The NO production by PMN did not appear to be related to cell viability or apoptosis. Indeed, neither the blockade of NO generation by L-NIO nor the incubation of the neutrophils with a NO donor, S-nitroso-acetylpenicillamine (SNAP) modified the pattern of LDH release or DNA fragmentation. In summary, it appears that PMN migration triggers a continuous NO synthesis, and that NO produced by these cells is not related to their apoptosis.